Remission of psoriasis and psoriatic arthritis during bevacizumab therapy for renal cell cancer - Ananaya Datta-Mitra; Navdeep K Riar; Siba P Raychaudhuri (Wolters Kluwer Medknow Publications, 2014)
Bevacizumab, a monoclonal antibody against vascular endothelial growth factor (VEGF), is employed for treatment of several cancers and retinopathies. Although previous reports of remission of psoriasis with bevacizumab do exist, but its current experience for psoriatic arthritis (PsA) is still limited. In this report, we describe a patient with metastatic renal cell cancer, psoriasis and PsA, who experienced a complete remission of psoriasis and PsA during bevacizumab therapy without any other management for psoriasis and PsA. We also found a flare up of his psoriatic disease after switching to other kinase inhibitors like sorafenib or sunitinib. This suggests that bevacizumab might have a promising future in the treatment of psoriasis and PsA.